2023
DOI: 10.3390/en16237794
|View full text |Cite
|
Sign up to set email alerts
|

Solar-Powered Water Electrolysis Using Hybrid Solid Oxide Electrolyzer Cell (SOEC) for Green Hydrogen—A Review

Shammya Afroze,
Amal Najeebah Shalihah Binti Sofri,
Md Sumon Reza
et al.

Abstract: The depletion of fossil fuels in the current world has been a major concern due to their role as a primary source of energy for many countries. As non-renewable sources continue to deplete, there is a need for more research and initiatives to reduce reliance on these sources and explore better alternatives, such as renewable energy. Hydrogen is one of the most intriguing energy sources for producing power from fuel cells and heat engines without releasing carbon dioxide or other pollutants. The production of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…AND ("enviro*" OR "ecolo*" OR "impact" OR "natural") 149 (49.3%) [66] In view of the results obtained in this bibliometric review, it can be seen that these challenges, which are identified by some authors, are also relevant for the rest of the scientific community, with aspects related to them appearing in more than 50% of the obtained results. The first of these challenges (Table 7) is the limited infrastructure for green hydrogen production, which poses significant challenges that must be addressed to realize its potential as a sustainable energy vector [57].…”
Section: Discussionmentioning
confidence: 88%
“…AND ("enviro*" OR "ecolo*" OR "impact" OR "natural") 149 (49.3%) [66] In view of the results obtained in this bibliometric review, it can be seen that these challenges, which are identified by some authors, are also relevant for the rest of the scientific community, with aspects related to them appearing in more than 50% of the obtained results. The first of these challenges (Table 7) is the limited infrastructure for green hydrogen production, which poses significant challenges that must be addressed to realize its potential as a sustainable energy vector [57].…”
Section: Discussionmentioning
confidence: 88%
“…Paper [92] proves that advancement in the PV industry and additional savings in the electrolyzer's electrical demand can further decrease the carbon footprint of yellow hydrogen. Produced from solar energy, yellow hydrogen can form the basis for the distributed production of smaller amounts of hydrogen needed to power individual hydrogen vehicles [93]. Photovoltaic systems placed on the roofs of houses, supported by energy storage, can provide enough energy to produce hydrogen to power several hydrogen vehicles.…”
Section: Introductionmentioning
confidence: 99%